The Yersinia enterocolitica pYV Virulence Plasmid Contains Multiple Intrinsic DNA Bends Which Melt at 37°C - Rohde, John R. (American Society for Microbiology, 1999)
Temperature has a pleiotropic effect on Yersinia enterocolitica gene expression. Temperature-dependent phenotypes include the switching between two type III protein secretion systems, flagellum biosynthesis (≤30°C) and virulence plasmid-encoded Yop secretion (37°C). The mechanism by which temperature exerts this change in genetic programming is unclear; however, altered gene expression by temperature-dependent changes in DNA topology has been implicated. Here, we present evidence that the Y. enterocolitica virulence plasmid, pYV, undergoes a conformational transition between 30 and 37°C. Using a simplified two-dimensional, single-gel assay, we show that pYV contains multiple regions of intrinsic curvature, including virF, the positive activator of virulence genes. These bends are detectable at 30°C but melt at 37°C, the temperature at which the cells undergo phenotypic switching. We also show that pACYC184, a plasmid used as a reporter of temperature-induced changes in DNA supercoiling, has a single region of intrinsic bending detected by our assay. Topoisomers of pACYC184, with and without this bend, isolated from Y. enterocolitica were resolved by using chloroquine gels. The single bend has a dramatic influence on temperature-dependent DNA supercoiling. These data suggest that the Y. enterocolitica pYV plasmid may undergo a conformational change at the host temperature due to melting of DNA bends followed by compensatory adjustments in superhelical density. Hence, changes in DNA topology may be the temperature-sensing mechanism for virulence gene expression in Y. enterocolitica and other enteric pathogens.